#TITLE_ALTERNATIVE# - ADITYA PERMADI (NIM 13204053), REZA
In this undergraduate thesis, many kinds of networks model, such as best effort, Diffserv, MPLS, and Diffserv over MPLS, will be implemented. The implementation will be done in a testbed consisting of several PC-based Linux router with the capability to understand MPLS and Diffserv mechanism. For each network model, TCP and UDP traffic will be generated with different characteristic identified by different bit rate. Diffserv network model will be able to classify packet based on its Type of Services, and give differential treatment to them. MPLS network model will be able to detect utilization of the links by identifying the bit rate of the traffic coming into the network interface. If it detects any congestion, several traffic will be routed into different route to avoid over-utilized links.